The Harvey girl - Stabenow, Dana (The Harvey Girls mysteries, 2026)
"1890. New Mexico. The New Mexico Territory is a lawless frontier where criminals steal money and land alike with impunity. Everyone wears a six-gun and is ready and willing to draw it. In the new city of Montaña Roja, Fred Harvey's growing empire is threatened by the robberies plaguing his newest Harvey House restaurant. To get justice, he needs a skilled detective to go undercover and procure answers to questions the law will not ask. The assignment falls to Clare Wright, a young Pinkerton agent. Disguised as one of Harvey's famous hostesses, Clare travels west where she risks being exposed at every step of her investigation. To get answers--and to get out alive--there are only two things she can trust: her instincts, and her derringer"--